Flying from History, Too Close to the Sun: The Anxious, Jubilant Futurism of Contemporary "Age of Man" Environmentalism - Obst, Arthur R. (Environmental ethics, 2023)
There is a remarkable trend in contemporary environmentalism that emphasizes "accepting responsibility" for the natural world in contrast to outdated preservationist thinking that shirks such responsibility. This approach is often explained and justified by reference to the anthropocene: this fundamentally new epoch - defined by human domination - requires active human intervention to avert planetary catastrophe. However, in this paper, I suggest this rhetoric encourages a flight from history. This often jubilant, sometimes anxious, yearning for unprecedented human innovation and - ultimately - control in our new millennia mirrors the Futurist movement that took off near the beginning of the last century. Despite the significant differences in the details of how academics have defended this twenty-first-century environmental outlook, they all represent the true flight from history; they too quickly jettison the ideas of historical environmentalists and so misunderstand the environmental values at the heart of preservation that are more salient than ever.